The postcolonial vortex - Photis Lysandrou; Yvonne Lysandrou (City, University of London, City Political Economy Research Centre (CITYPERC), 2023)
The subject of this paper is the contemporary postcolonial condition. Its central argument is that this condition is one of perpetual entrapment in circular motion as any progression registered by postcolonial countries by participating in the global capitalist system as independent states is continually offset by a backward-pulling regression arising out of their subordinate position in that system. This entrapment in 'proregression', to abbreviate the progression-regression nexus, is not in itself a new experience for postcolonial countries. What is new is the primary mechanism that perpetuates proregression: where in the previous eras of colonialism and neo-colonialism that primary mechanism rested on the force of authority, in the current postcolonial era it rests on the force of gravity. It is testimony to the strength of this force that even those emerging capitalist countries that have never been the subject of external control in the colonial era are now also caught in the predicament of proregression. However, the fact that the postcolonial countries have previous experience of proregression makes their present experience going forward even more acute. It is as if their history is caught in an endless series of overlapping cycles, as each mode of progression on a higher plane of development is countered by a mode of regression on an equivalent plane of development. In short, it is as if their whole history is caught in a vortex.
Keywords: 330